Strategi Peningkatan Keterampilan Kemampuan Berkomunikasi Bagi Siswa Sekolah Kewirausahaan Cordova - GUNAWAN PUTRA, ANDREAS WAHYU; Lukito, Nico (PT. Cendekia Sapta Indonesia, 2025)
S In the post-pandemic era, small and medium enterprises (SMEs) are required to strengthen communication skills to manage their businesses effectively. The Cordova School of Entrepreneurship, as a partner in developing young entrepreneurs, faces challenges in communication skills, both within teams and with customers. This community service program (PkM) aimed to enhance the communication skills of Cordova students through training in effective communication techniques. The implementation method included workshops, presentations, discussions, and case consultations. A total of 22 participants attended the program on December 17, 2023. The evaluation results indicate improved understanding of communication planning, channel selection, public speaking, and the linkage between communication strategies and target market determination. Participants demonstrated high enthusiasm during the discussions and expressed interest in further mentoring to apply communication strategies. This program provides tangible benefits in strengthening the communication capacity of SMEs, which is expected to improve their business competitiveness in the post-pandemic era. In the future, the program has the potential to be expanded through continuous mentoring and integration with SME digitalization initiatives.